ASSESSMENT OF MEDICATION ADHERENCE AMONG ELDERLY PATIENTS IN MYSURU CITY - KUMAR, JAIDEV; MAHENDRAPPA; KUMAR, PRAMOD (International Journal of Current Pharmaceutical Research, 2019)
Objective: To assess medication adherence among patients with chronic diseases. Methods: This was a prospective observational study carried out over period of one year in mysuru city. The subjects who meet study criteria were enrolled in this research study. The enrolled subjects were administered with simplified medication adherence questionnaire. The criteria to establish adherent and non-adherent were calculated as per simplified medication adherence questionnaire directions. Results: The gender distribution of this research study was reflected with male accountable for 45.63 % followed by female 54.36%. Asper simplified medication adherence questionnaire88% were adherent and remaining 12% were non-adherent in this research study. Conclusion: Patients with good adherence in this research study showed that they have good literacy status as well as better awareness about the existing medical condition and more consciousness may be there among these patients, what will be going to happen if their medical condition is left untreated.46.29 % males and 59.58 % females were adherent in this research study followed by 59.24% were adherent in the age range of 60-70 y as they were more conscious and less forgetfulness about medications as per the directions given by patient consultant which was oral feedback taken by research investigators during medication review in subjects home.